Community Relations Management in Developing an Educational Institution at Junior High School State 2 Tondano, Minahasa District - Tambingon, Henny; Lengkong , Jeffry Sony Junus; Rawis, Joulanda A.M.; Kambu, Kornelius; Rattu, Olviane I.; Paat, Wensi R. L. (JR Education, 2024)
Society and schools are an inseparable unit to educate the nation's children. Both are part of the center of the tricenter of education. This research aims to describe public relations management (PR) in developing educational institutions. The background of this research is Middle School in Minahasa Regency. This study uses an approach qualitative with descriptive study methods. Data collection was carried out through interview techniques, observation, and document study. Furthermore, data analyzed use technique reduction, presentation data, And withdrawal conclusion. Testing the validity of the data was obtained through triangulation techniques. The results of this research show that public relations management at SMP Negeri 2 Tondano is carried out well, this is seen from the implementation of management functions in developing the school. Furthermore, public relations performance is carried out well, in the form of direct involvement with student guardians, government and related agencies, committees, and the community general, added Again with involvement field public relations in socialization on line school the on various social media.